An environmental study of organic pollutants in Shatt al-Basra waters - Suha waleed Mustafa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study focused on measuring the concentrations of organic pollutants in the artificial waters of the Shatt al-Basra canal for the period from June 2018 to July 2019, and samples were collected from four sites distributed along the canal. At a rate of (32.3) NTU, and the EC values ​​were within the baseline at a rate of (7.4). The seasonal significant differences for the CO2 values ​​were evident, as the winter season recorded the highest values ​​at a rate of (210.5) mg / liter, and the rates of BOD5 exceeded (5.5) mg / L and D.O (3.8) mg / liter, the permissible limits for most sites, with significant differences for both dimensions, and the overall rate of TSS was (4884.8) mg / liter, and TH values ​​increased in all sites with values ​​exceeding the limits and a rate of (4279.6) mg / liter.DOI /10.54633/2333-021-042-028